(untitled) (Research, Society and Development, 2021)
This research aimed to understand how social participation is developed in the Municipal Health Council, in the city of Rio Branco/Acre-Brasil. A qualitative approach and case study methodology were used. The investigation was carried out in stages, namely: monitoring of the meetings of that body, using the technique known as systematic observation; the second consisted of document analysis of the minutes of the meetings and management documents; and, conducting interviews with all counselors. This council presented the following obstacles to its implementation and real democratization of the management of public health policies as obstacles: asymmetrical power relations; representation difficulties, especially in the user segment; lack of training for the full exercise of the mandate of a councillor. There is a potential for sharing power and responsibilities in spaces like these, and the actors involved must have their effort to participate valued and encouraged, giving them a voice and listening and having their interventions and/or requests met.